2022
DOI: 10.3390/ijms231912014
|View full text |Cite
|
Sign up to set email alerts
|

Virus-Associated Nephropathies: A Narrative Review

Abstract: While most viral infections cause mild symptoms and a spontaneous favorable resolution, some can lead to severe or protracted manifestations, specifically in immunocompromised hosts. Kidney injuries related to viral infections may have multiple causes related to the infection severity, drug toxicity or direct or indirect viral-associated nephropathy. We review here the described virus-associated nephropathies in order to guide diagnosis strategies and treatments in cases of acute kidney injury (AKI) occurring … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 298 publications
0
11
0
Order By: Relevance
“…Kidney injury is a complex disease that is characterized by the impairment of renal function. It has been previously reported that a variety of pathogenic factors can lead to kidney injury, such as some drugs and a majority of toxics [14]. Moreover, sepsis has also been reported to serve as an important pathogenic factor that contributes to kidney injury [15].…”
Section: Discussionmentioning
confidence: 99%
“…Kidney injury is a complex disease that is characterized by the impairment of renal function. It has been previously reported that a variety of pathogenic factors can lead to kidney injury, such as some drugs and a majority of toxics [14]. Moreover, sepsis has also been reported to serve as an important pathogenic factor that contributes to kidney injury [15].…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, several studies have also shown the crucial role of infections in causing glomerulonephritis [ 59 ] and confirmed the main role of extrahepatic infection of the hepatitis B (HBV) and C (HCV) viruses [ 60 , 61 ] ( Table 1 ). Furthermore, other works highlighted the relationship between occult HCV/HBV infections and GN.…”
Section: Hepatitis B and C And Glomerulonephritismentioning
confidence: 73%
“…Patients may also have a protracted course of HBV-related mixed cryoglobulinemia (MC), often with severe renal manifestations involving nephrotic-range proteinuria and acute kidney disease (AKI) [ 59 ].…”
Section: Hepatitis B and C And Glomerulonephritismentioning
confidence: 99%
See 1 more Smart Citation
“…[ 135 ] Although not yet fully understood, some mechanisms suggested as causes of AKI in severe dengue are hypotension – leading to hypoperfusion and tubular necrosis – direct injury caused by the virus, indirect injury via the immune system, and rhabdomyolysis. [ 136 , 137 ] Immunohistochemical studies performed on kidney specimens from fatal human cases of dengue infection found viral RNA and observed an accumulation of immune cells and intense acute congestion, suggesting that a combination of high viral load, exacerbated immune response, and increased permeability play a role in renal damage during dengue infection. [ 138 , 139 ]…”
Section: Organ Dysfunctionsmentioning
confidence: 99%